2020
DOI: 10.1038/s41398-020-0774-1
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline-induced microbiome alterations predict cafeteria diet-induced spatial recognition memory impairments in rats

Abstract: Diets rich in sugar and saturated fat are associated with cognitive impairments in both humans and rodents with several potential mechanisms proposed. To test the involvement of diet-induced pro-inflammatory signaling, we exposed rats to a high-fat, high-sugar cafeteria diet, and administered the anti-inflammatory antibiotic minocycline. In the first experiment minocycline was coadministered across the diet, then in a second, independent cohort it was introduced following 4 weeks of cafeteria diet. Cafeteria d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 70 publications
(66 reference statements)
3
17
2
Order By: Relevance
“…Dietary factors are a key source of gut microbiome diversity 28,46,[61][62][63] and emerging evidence indicates that diet-induced alterations in the gut microbiota may be linked with altered neurocognitive development 28,[63][64][65] . Our results identify species within the genus Parabacteroides that are elevated by habitual early life consumption of dietary sugar and are negatively associated with hippocampal-dependent memory performance.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary factors are a key source of gut microbiome diversity 28,46,[61][62][63] and emerging evidence indicates that diet-induced alterations in the gut microbiota may be linked with altered neurocognitive development 28,[63][64][65] . Our results identify species within the genus Parabacteroides that are elevated by habitual early life consumption of dietary sugar and are negatively associated with hippocampal-dependent memory performance.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate these findings suggest that beneficial effects of minocycline on HFD-induced metabolic dysfunction may be regulated, at least in part, via selective reductions in PVN neuroinflammatory processes. Although not tested here, minocycline has been suggested to modulate high fat diet outcomes via alteration of the gut microbiome ( Hasebe et al, 2019 ; Leigh et al, 2020 ; Vaughn et al, 2017 ), which has also been shown to alter neuroinflammatory signaling ( Haase et al, 2020 ; Rea et al, 2016 ; Rutsch et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Odoribacter level increased significantly in APP/PS1 [ 72 ] and aged [ 73 ] mice with impaired spatial learning. Desulfovibrio was also associated with memory decline, induced by a high-fat diet [ 74 , 75 ]. At the same time, some of our data are at odds with the previously obtained results.…”
Section: Discussionmentioning
confidence: 99%